2023
DOI: 10.15252/embj.2021110468
|View full text |Cite
|
Sign up to set email alerts
|

Caspase‐8‐driven apoptotic and pyroptotic crosstalk causes cell death and IL‐1β release in X‐linked inhibitor of apoptosis (XIAP) deficiency

Abstract: Genetic lesions in X‐linked inhibitor of apoptosis (XIAP) pre‐dispose humans to cell death–associated inflammatory diseases, although the underlying mechanisms remain unclear. Here, we report that two patients with XIAP deficiency–associated inflammatory bowel disease display increased inflammatory IL‐1β maturation as well as cell death–associated caspase‐8 and Gasdermin D (GSDMD) processing in diseased tissue, which is reduced upon patient treatment. Loss of XIAP leads to caspase‐8‐driven cell death and bioac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 107 publications
0
7
0
Order By: Relevance
“…Notably, the PAO1-induced accumulation of cleaved GSDME in neutrophils was not inhibited by ZVAD. Lien et al and Poltorak et al showed that caspase-8 mediates GSDMD processing in Yersinia infected macrophages 27 , 28 , and Vince et al 29 recently reported that caspase-8 is associated with GSDMD cleavage in macrophages from patients with mutations in the X-linked inhibitor of apoptosis protein (XIAP) and in murine macrophages incubated with IAP antagonists. However, although caspase-8 was cleaved in TNF/SM treated macrophages and neutrophils, caspase-8 was not cleaved following PAO1 infection (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, the PAO1-induced accumulation of cleaved GSDME in neutrophils was not inhibited by ZVAD. Lien et al and Poltorak et al showed that caspase-8 mediates GSDMD processing in Yersinia infected macrophages 27 , 28 , and Vince et al 29 recently reported that caspase-8 is associated with GSDMD cleavage in macrophages from patients with mutations in the X-linked inhibitor of apoptosis protein (XIAP) and in murine macrophages incubated with IAP antagonists. However, although caspase-8 was cleaved in TNF/SM treated macrophages and neutrophils, caspase-8 was not cleaved following PAO1 infection (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Its functional role depends on the interplay with other partners, and even subtle alterations in the composition of caspase-8 complexes can give rise to contradicting physiological outcomes, such as the switching between macrophage death modalities or between cell death and cell activation ( 119 ). Notably, in the absence of an X‐linked inhibitor of apoptosis (XIAP), extrinsic caspase-8 promotes pyroptotic GSDMD processing, resulting in the demise of macrophages lacking both inflammasome and apoptosis signaling components (caspase-1, -3, -7, -11 and BID) ( 124 ). In addition to RIPK1, caspase-8 can cleave RIPK3 ( 125 ).…”
Section: Cross-interactions Among Pyroptosis Necroptosis and Ferropto...mentioning
confidence: 99%
“…Other examples of cross-talk between RCD include the link between ferroptosis and autophagy, in particular through ferritin degradation or the involvement of lysosomes in iron storage and redistribution [47,48] . Depletion of the ferroptosis trigger GPX4 also sensitizes cells to pyroptosis [49] , necroptosis [50] and apoptosis [51] . Apoptosis and necroptosis are also linked through caspase 8 cleavage [Figure 1].…”
Section: Other Cell Death Pathwaysmentioning
confidence: 99%
“…Apoptosis and necroptosis are also linked through caspase 8 cleavage [ Figure 1 ]. Caspase 8 is also an important player in pyroptosis induction, as it has been shown that genetic lesions in XIAP result in increased inflammation and death-associated caspase-8 and GSDMD processing in diseased tissue [ 52 ] . Common stimuli can also result in different RCD depending on the cell type.…”
Section: Regulated Cell Death Pathwaysmentioning
confidence: 99%